THE DIFFERENCES BETWEEN DEPRESSION LEVEL BEFORE AND AFTER BEING GIVEN LOGOTHERAPY IN CANCER CLIENTS AT KEN SARAS HOSPITAL SEMARANG REGENCY - Abdul Wakhid; Shofhatun Nadhiyat; Sukarno Sukarno; Dewi Rosnita (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2018)
Cancer is one of the most feared diseases that cause death. The most common psychological problem found in cancer clients is depression which can affect the treatment, extend the hospitalization time, decreases the therapeutic process, and client's survival. To overcome the problem on the client, nursing intervention can be given in the form of logotherapy. The purpose of this study is to determine the differences between depression levels before and after logotherapy in cancer client at Ken Saras Hospital, Semarang Regency. This research design used pre-experiment with one group pre-posttest design. The population of this study was cancer patients at Ken Saras hospital as many as 22 respondents by using purposive sampling technique and data collecting tool used Back Depression Inventory. Data analysis used t-test dependent test. The results show that the depression level of cancer clients before logotherapy is mostly in moderate category (86,4%), the depression level of cancer clients after logotherapy is mostly in mood disorder (63,6%). There are differences between depression levels before and after logotherapy of cancer client at Ken Saras Hospital, Semarang Regency, with p value (0,000) <α (0,05). Ken Saras hospital should utilize logotherapy as a complementary therapy to support the psychological side of cancer patients so that the healing process can run optimally. Keywords: Logotherapy, Depression Level, Cancer